Dataset related to sub-study one of the PainSMART-project (RCT-PROMs primary and secondary outcomes). - Thompson, Richard (Linköping University, 2026)
Data supporting the results of this study comprise patient reported outcome measures (PROMs) and baseline information used as covariates in adjusted models.

Data were collected for the two groups (PainSMART-group and Control Group) via online questionnaires at four time points: Baseline, follow-up 1 (24-72 hours pre-initial physiotherapy consultation), follow-up 2 (24 hours post-initial physiotherapy consultation) and follow-up 3 (three months post-baseline).

The following PROMs were collected:

Primary outcomes

-    Average pain intensity in the last 24 hours (NRS-average pain, 0-10).

-    Pain self-efficacy (Pain Self Efficacy Questionnaire, PSEQ-10, 0-60).

Secondary outcomes

-    Best pain intensity in the last 24 hours (NRS-best pain, 0-10).

-    Worst pain intensity in the last 24 hours (NRS-worst pain, 0-10).

-    MSKP-related illness perceptions (Brief Illness Perception Questionnaire, BIPQ, 0-80).

-    MSKP-management strategies (Brief Pain Coping Inventory-2:SWE Traditional Pain Management Strategies subscale, BPCI-2:SWE TPMS, 0-56).

-    Psychological flexibility (BPCI-2:SWE Psychological Flexibility, PF-subscale, 0-77).

-    Reassurance of the benign nature of MSKP (NRS-reassurance, 0-10).

-    Self-reported physical activity levels in the preceding week (FASTA-score, 3-19).

- Self-reported sitting time (hours per day, 0-16hrs).

- Global rating of change scale (GRoC, -5 to +5).

The following baseline covariates were used to adjust the models.

Age, biological sex, body-mass-index, highest educational level, comorbidities (yes/no), work status (working/not working), sickness absence (absent/not absent), pain duration (acute/chronic with 3-month cut-off), pain localisation (regional pain/widespread pain), time from baseline to consultation (days), healthcare consultations for presenting MSKP in preceding 3-months (yes/no), Örebro Musculoskeletal Pain Screening Questionnaire (ÖMPSQ) risk category (high >50 points or low ≤50), analgesic use (yes/no).

LiU secure repository is a data repository that hosts research data which cannot be openly available for ethical or legal reasons. LiU secure repository is managed by Linköping University Library as a service to researchers at Linköping University (Sweden). For requests of access or further information, please contact datamanagement@liu.se
Keywords: Pain; Health Sciences; Hälsovetenskap